Phosphorus-containing polyimide fibers and their thermal properties. Issue 44 (18th April 2016) - Serbezeanu, Diana; Butnaru, Irina; Varganici, Cristian-Dragos; Bruma, Maria; Fortunato, Giuseppino; Gaan, Sabyasachi
Abstract : Submicron fibers based on phosphorus-containing polyimide were successfully prepared and characterized for their thermal properties. Abstract : Phosphorus-containing polyimide was synthesized by solution polycondensation reaction of bis(3-aminophenyl) methyl phosphine oxide with 4, 4′-(4, 4′-isopropylidenediphenoxy)bis(phthalic anhydride). The chemical characterization of polyimide was done using FTIR and NMR spectroscopy. Also, the influence of different parameters on the rheological and thermal behavior of the polyimide was investigated. We were able to prepare uniform submicron- or nano-sized fibers by electrospinning highly viscous polyimide solutions. The diameters of the electrospun fibers increased from 58 nm to 347 nm as the concentration of the polyimide solution was raised from 10 to 24 wt%. Isoconversional kinetic analysis of the thermal decomposition of the polyimide was performed using Friedman and Ozawa–Flynn–Wall methods. The thermal decomposition mechanism of polyimide was evaluated and proposed using thermogravimetric analyzer-Fourier transform infrared spectroscopy (TGA-FTIR) and pyrolysis gas chromatography mass spectroscopy (Py-GC-MS). The results showed a complex degradation process of the main chain, which started with the scission of weaker bonds such as ether, alkyl, imide and some aromatic groups. The char residue of the polyimide fibers from TGA experiments were analyzed using scanning electron microscopy (SEM). It exhibited a dense structure, with a homogeneous dispersion of phosphorus atoms.